Increasing the Conversion of Hyoscyamine to Scopolamine in Stable Autotetraploid Plants of Egyptian Henbane (Hyoscyamus muticus) - E Dehghan; E Ghotbi Ravandi; H Naghdi Badi; A Tanhaeian; B Hosseini Khalifani (Institue of Medicinal Plants, ACECR, 2012)
Background : Ploidy manipulation is always accompanied by conspicuous changes in morphology and biochemical characteristics in plants. So that it is suggested as a rapid and useful strategy for breeding the quality and quantitative traits related to the secondary metabolite production in medicinal plants. Egyptian henbane is one of the most important sources of tropane alkaloids specially hyoscyamine and a trace of scopolamine.   Objectives : The main objects of this research were study of the stability of ploidy manipulation and its effects on the qualitative and quantitative changes of tropane alkaloid production in Hyoscyamus muticus plant.   Methods : The stability of ploidy level in autotetraploid plants (that already obtained by colchicine treatment) of Egyptian henbane was investigated by morphological, microscopic and flow cytometry methods. The changes in the production of tropane alkaloid compounds were also analyzed by GC-MS in diploid and tetraploid plants.   Results : The results of morphologic, microscopic and flow cytometry methods confirmed the stability of autotetraploidy in Egyptian henbane plant. Tetraploid plants showed a higher potential in production of scopolamine, than diploid ones. Conclusion : Regard to the higher commercial value of scopolamine than other tropane alkaloid coumpounds, Ploidy manipulation can efficiently be used to improve scopolamine production in Hyoscyamus muticus plant.